2013
DOI: 10.1074/jbc.m113.455667
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of Plasmodium falciparum 12 (Pf12) Reveals a Unique Interdomain Organization and the Potential for an Antiparallel Arrangement with Pf41

Abstract: Background: Pf12 is the archetypal member of the 6-Cys protein family, members of which are important Plasmodium vaccine targets. Results: Purifying selection and apical localization of Pf12, crystal structure of tandem 6-Cys domains, and mass spectrometry of cross-linked Pf12-Pf41 heterodimer are shown. Conclusion: A functionally important role for Pf12 and potential for antiparallel heterodimer is provided. Significance: First full-length 6-Cys protein structure and first details of heterodimer organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 67 publications
5
98
0
Order By: Relevance
“…Pfs230D1M appeared comparable biochemically and biophysically to Pfs230D1H with the exception of the designed changes. In addition, the two disulfide bonds within Pfs230D1M were mapped and assigned as C1 to C2 and C3 to C4, which was in agreement with the NMR analysis of recombinant Pfs12, another malaria protein with a comparable 6-cysteine-rich motif (29). It is interesting to note that the latter disulfide is homologous to the C3-C6 disulfide pairing observed for Pf12 and Pf41 (29,30).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Pfs230D1M appeared comparable biochemically and biophysically to Pfs230D1H with the exception of the designed changes. In addition, the two disulfide bonds within Pfs230D1M were mapped and assigned as C1 to C2 and C3 to C4, which was in agreement with the NMR analysis of recombinant Pfs12, another malaria protein with a comparable 6-cysteine-rich motif (29). It is interesting to note that the latter disulfide is homologous to the C3-C6 disulfide pairing observed for Pf12 and Pf41 (29,30).…”
Section: Discussionsupporting
confidence: 62%
“…Structural Modeling-The comparative model of Pfs230D1M was constructed with Rosetta (44) using the crystal structures of Pf12, PDB code 2YMO (29), and Pf41, PDB code 4YS4 (30), as templates. Secondary structure analysis was performed with STRIDE (45).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of Pfs47 in 364 worldwide P. falciparum isolates (Dataset S1) allowed us to identify 47 different DNA haplotypes (Dataset S2) that exhibit a high ratio of nonsynonymous/synonymous (dN/dS = 30) substitutions, in agreement with previous reports (22) and indicative of selection. Pfs47 has three s48/45 domains and most polymorphisms are present in the second domain (D2) (SI Appendix, Fig.…”
Section: Mosquito Antiplasmodial Immunity Mediates the Incompatibilitysupporting
confidence: 65%
“…While epitope analysis of Pfs48/45 has revealed surface targets of transmission blocking monoclonal antibodies [46], lack of any structural information and knowledge of conformational target epitopes has resulted in limited success in the development of recombinant TBV based on Pfs48/45. Computational modeling [6] and experimental structure determination [47, 48] approaches have been used to predict structure of Pfs48/45. However, reproducible production of correctly folded recombinant protein remains a challenge and the immunization studies thus far have revealed efficacies not ideal for vaccine development.…”
Section: Discussionmentioning
confidence: 99%